2021
DOI: 10.1111/1749-4877.12570
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interactions between pterin and carotenoid genes modulate intra‐morph color variation in a lizard

Abstract: Color polymorphisms have become a major topic in evolutionary biology and substantial efforts have been devoted to the understanding of the mechanisms responsible for originating such colorful systems. Within‐morph continuous variation, on the other hand, has been neglected in most of the studies. Here, we combine spectrophotometric/visual modeling and genetic data to study the mechanisms promoting continuous variation within categorical color morphs of Podarcis muralis. Our results suggest that intra‐morph va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, it should be noted that, since the alleles that are associated with orange and yellow pigmentation have a recessive mode of inheritance, it is possible that some populations still retain this variation at very low levels. Furthermore, the presence of the yellow carotenoid‐based colouration can also be masked by orange pterins in the skin (Aguilar, Andrade, & Pérez i de Lanuza, 2022; Andrade et al., 2019), which could lead to underestimating the frequency of the ‘ y ’ allele. Supporting this, all populations included at least a few yellow and/or yellow‐orange individuals, thus evidencing the persistence of the ‘ y ’ allele, even if at low frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that, since the alleles that are associated with orange and yellow pigmentation have a recessive mode of inheritance, it is possible that some populations still retain this variation at very low levels. Furthermore, the presence of the yellow carotenoid‐based colouration can also be masked by orange pterins in the skin (Aguilar, Andrade, & Pérez i de Lanuza, 2022; Andrade et al., 2019), which could lead to underestimating the frequency of the ‘ y ’ allele. Supporting this, all populations included at least a few yellow and/or yellow‐orange individuals, thus evidencing the persistence of the ‘ y ’ allele, even if at low frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…For the yellow locus, however, we cannot calculate the allelic frequencies as above, because orange colouration is epistatic over yellow (Aguilar, Andrade, & Pérez i de Lanuza, 2022; Andrade et al., 2019). Thus, a portion of the orange morph individuals would also carry one or two copies of the recessive allele at the yellow locus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our study shows a negative effect of a road on the nearby habitat and its influence on the expression of the sexual coloration in lizards that suffered an additional stress stimulus (translocation). Moreover, recent research showed that epistatic interactions between pteridine and carotenoid regulatory genes influence colour patch expression in lacertids (Aguilar et al 2022). Therefore, as phenotypic traits result from the interaction between genotype and environment, whether the differential expression of male sexual coloration between the two lineages of P. algirus is influenced by the environment guarantees further investigation.…”
Section: Further Implications and Future Directionsmentioning
confidence: 99%
“…Finally, colour alleles may counterbalance the build-up of population structure by acting as genomic bridges between morphs (Comeault et al, 2015). In fact, white individuals can carry orange (o) and yellow alleles (y) in heterozygosity, while orange lizards can present every genotype at the yellow locus (YY, Yy or yy); thus, offspring of P. muralis will not always express the same phenotype as their parents (Abalos et al, 2022;Aguilar et al, 2022;Andrade et al, 2019). Mosaic morphs (i.e., whiteorange and yellow-orange) may also facilitate gene flow between colour morphs, but further work is needed to understand their basis and role in the maintenance of colour morphs of P. muralis.…”
Section: Genomic Differentiation Between Individuals Analysed In Thismentioning
confidence: 99%